2014
DOI: 10.1039/c4ra00904e
|View full text |Cite
|
Sign up to set email alerts
|

A novel fuel cell membrane with high efficiency

Abstract: A novel polymer containing an azo based ionic diol has been successfully fabricated as an electrolyte membrane to yield a good fuel cell performance in the whole range of current density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…The detailed procedure for the electrochemical performance studies was reported in our earlier article. 34…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The detailed procedure for the electrochemical performance studies was reported in our earlier article. 34…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The proton conductivity measurements of the samples were carried out by our earlier reported article. 23…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Water uptake ability and swelling ratio of the electrolyte membranes were measured as per the procedure reported in our previous study. 42 Thermogravimetric analysis (TGA) was used to investigate the thermal stability of the polymers. Samples were heated from room temperature to 600 C at the rate of 10 C min À1 under a N 2 atmosphere.…”
Section: Measurementsmentioning
confidence: 99%